An atomic clock synchronized versatile all-in-one digital ‘LockBox’ - S. Johnson; S. Das Gupta; T. R. Saravanan; S. Banerjee; S. Majhi; S. De (Scientific Reports)
Abstract A reliable and robust active stabilization of different control parameters is key to the success of many experiments. The essential hardware for that; lock-in detection, RF generator, and proportional-integral-derivative feedback control should have sufficient bandwidth, low noise operation and versatility to use the system in different applications. Here we report a fully digital, all essential requirements in one system (LockBox), featured with complete control cum monitoring of the signals from a touchscreen display and the possibility of operating from a remote PC. The lock-in in it has DC to 840 kHz bandwidth, the sinusoidal generator for RF modulation is up to 62.5 MHz, the system noise is 13.2 $$\textrm{nV}_{\textrm{rms}}/\sqrt{\textrm{Hz}}$$ at 100 kHz, and referenced to a Rubidium-clock. We have demonstrated its use for stabilization of laser frequency using an emulated Pound-Drever-Hall and a fiber spool as two independent references, and also for arm length locking of a Michelson interferometer.